Africa in global politics in the twenty-first century a pan-African perspective - Abegunrin, Olayiwola (New York Palgrave Macmillan, 2009)
In this twenty-first century, Africa has become an important source of the United States? energy imports and the world's natural resources. It has also become the epicenter of the world?s deadly health epidemic, HIV/AIDS, and one of the battlegrounds in the fight against terrorism. With Nigeria and South Africa leading the continent, Africa has become a major player to be reckoned with in the global affairs.
Includes bibliographical references and index.
Keywords: World politics-21st century. Africa, Sub-Saharan-Foreign relations-1960- Africa, Sub-Saharan-Politics and government --1960- Africa, Sub-Saharan-Social conditions-1960- Nigeria-Foreign relations-1960- Nigeria-Politics and government -1960- Nigeria-Social conditions-1960- South Africa-Foreign relations -1994- South Africa-Politics and government -1994- South Africa-Social conditions-1994-